2020
DOI: 10.4093/dmj.2020.0058
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Obesity on the Sense of Taste: Taste Buds as Treatment Targets?

Abstract: Premature obesity-related mortality is caused by cardiovascular and pulmonary diseases, type 2 diabetes mellitus, physical disabilities, osteoarthritis, and certain types of cancer. Obesity is caused by a positive energy balance due to hyper-caloric nutrition, low physical activity, and energy expenditure. Overeating is partially driven by impaired homeostatic feedback of the peripheral energy status in obesity. However, food with its different qualities is a key driver for the reward driven hedonic feeding wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 173 publications
0
47
0
3
Order By: Relevance
“…Obesity is a complex disease that is driven by a combination of several genetic and lifestyle factors including excess consumption of calorie-rich diets and sedentary behaviour [35]. There is growing evidence that diet-induced obesity can alter the oral gustatory pathways, thus affecting nutritional intake and further exacerbating the condition [22,[36][37][38]. Though several system-wide studies have investigated the effects of HFD consumption on whole body metabolism, none have reported on any associated changes occurring in the orosensory pathways [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a complex disease that is driven by a combination of several genetic and lifestyle factors including excess consumption of calorie-rich diets and sedentary behaviour [35]. There is growing evidence that diet-induced obesity can alter the oral gustatory pathways, thus affecting nutritional intake and further exacerbating the condition [22,[36][37][38]. Though several system-wide studies have investigated the effects of HFD consumption on whole body metabolism, none have reported on any associated changes occurring in the orosensory pathways [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In fact studies of calorie restriction-induced weight loss and bariatric surgery in humans have suggested that taste alterations and food preferences are reversible and consequently may represent secondary effects of obesity [60][61][62][63][64]. However, the possibility cannot be ruled out that other factors than weight loss per se, such as reward value and gut-brain-interactions, drive the observed modifications in taste perception [65]. Furthermore, some studies that considered obese individuals after bariatric surgery also reported a lower intake and liking of high-fat and sweet foods [66].…”
Section: Article In Pressmentioning
confidence: 99%
“…Angiotensin inhibits salty taste and enhances sweet taste sensitivities [ 57 ] while leptin selectively suppresses neural and behavioral responses to sweet taste [ 58 ]. Various research groups have tried to define the expression patterns and roles in taste perception of the hormones, which are well described in other review articles [ 59 , 60 ].…”
Section: Hormonal Effects On Taste Perceptionmentioning
confidence: 99%